2000
DOI: 10.1002/1521-3757(20001215)112:24<4736::aid-ange4736>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Benzene-Centered Tri- and Tetrametallacarborane Sandwich Complexes

Abstract: Mehrere Metallacarboran‐Einheiten an einem zentralen Benzolring zu verankern gelang mit der Bor‐Überdachungs‐Methode. Im FeCo3‐Komplex 1 sowie in dessen Vorstufe dient der Benzolring zur Verknüpfung der Metallacarboran‐Einheiten. Somit sollten diese Komplexe für die Bildung mehrkerniger, gemischtvalenter, elektronendelokalisierter Systeme durch Redoxprozesse geeignet sein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…For nearly almost half a century, interests in the chemistry of carboranes and metallacarboranes have been extended to the electrical, magnetic, and NLO properties since they were first discovered and characterized in the 1960s. However, compared to the most well-known and extensively studied example of closo-carboranes like icosahedral ortho- , meta- , and para- C 2 B 10 H 12 , systematic studies of nido-carborane (nest-like) such as [C 2 B 4 H 6 ] 2– or [C 2 B 9 H 11 ] 2– and arachno-carborane (cobweb-like) such as [C 2 B 3 H 5 ] 4– have remained exceedingly rare up to now. , In the preceding publications, Grimes and co-workers have described the synthesis of several families of metallacarborane sandwich complexes like cobaltacarboranes and ferracarboranes, which covalently bound aryl- and alkynyl-linked polynuclear metallacarboranes that incorporate MC 2 B 4 clusters (Scheme ). Meanwhile, in these metallacarborane complexes, it has been demonstrated that the pyramidal Et 2 C 2 B 4 H 4 2– carborane ligand has strong electron-donating properties. Hence, within individual sandwich unit (Et 2 C 2 B 4 H 4 )­Fe­(η 6 -C 6 H 6 ), the electron density would flow from the ferracarborane cluster to the ferrocenyl moiety.…”
Section: Introductionmentioning
confidence: 99%
“…For nearly almost half a century, interests in the chemistry of carboranes and metallacarboranes have been extended to the electrical, magnetic, and NLO properties since they were first discovered and characterized in the 1960s. However, compared to the most well-known and extensively studied example of closo-carboranes like icosahedral ortho- , meta- , and para- C 2 B 10 H 12 , systematic studies of nido-carborane (nest-like) such as [C 2 B 4 H 6 ] 2– or [C 2 B 9 H 11 ] 2– and arachno-carborane (cobweb-like) such as [C 2 B 3 H 5 ] 4– have remained exceedingly rare up to now. , In the preceding publications, Grimes and co-workers have described the synthesis of several families of metallacarborane sandwich complexes like cobaltacarboranes and ferracarboranes, which covalently bound aryl- and alkynyl-linked polynuclear metallacarboranes that incorporate MC 2 B 4 clusters (Scheme ). Meanwhile, in these metallacarborane complexes, it has been demonstrated that the pyramidal Et 2 C 2 B 4 H 4 2– carborane ligand has strong electron-donating properties. Hence, within individual sandwich unit (Et 2 C 2 B 4 H 4 )­Fe­(η 6 -C 6 H 6 ), the electron density would flow from the ferracarborane cluster to the ferrocenyl moiety.…”
Section: Introductionmentioning
confidence: 99%